Detoxification of Chemical Warfare Agents Using a Zr6‐Based Metal–Organic Framework/Polymer Mixture. Issue 42 (8th September 2016) - Moon, Su‐Young; Proussaloglou, Emmanuel; Peterson, Gregory W.; DeCoste, Jared B.; Hall, Morgan G.; Howarth, Ashlee J.; Hupp, Joseph T.; Farha, Omar K.
Abstract: Owing to their high surface area, periodic distribution of metal sites, and water stability, zirconium‐based metal–organic frameworks (Zr6 ‐MOFs) have shown promising activity for the hydrolysis of nerve agents GD and VX, as well as the simulant, dimethyl 4‐nitrophenylphosphate (DMNP), in buffered solutions. A hurdle to using MOFs for this application is the current need for a buffer solution. Here the destruction of the simulant DMNP, as well as the chemical warfare agents (GD and VX) through hydrolysis using a MOF catalyst mixed with a non‐volatile, water‐insoluble, heterogeneous buffer is reported. The hydrolysis of the simulant and nerve agents in the presence of the heterogeneous buffer was fast and effective. Abstract : A heterogeneous catalyst system consisting of a Zr‐MOF and cationic polymer could effectively detoxify not only a nerve agent simulant, dimethyl 4‐nitrophenylphosphate, but also nerve agents, GD and VX, in water. This heterogeneous mixture was prepared as a composite with cellulose fiber, which can be used in protective gear such as masks, suits, gloves, and cleaning mats.